Incorrect arguments of scientific discourse in pedagogical texts, or samples for non-imitation - A. V. Korzhuev; N. V. Golovina; N. A. Kontarov; Yu. B. Ikrennikova (Russian State Vocational Pedagogical University, 2024)
Introduction. Modern humanities are moving towards compliance with the requirement of evidence and comprehensive validity of their conclusions, the adequacy of the methods used and research strategies to the results obtained. This problem can be briefly summarised as a movement towards argumentative correctness. In the sciences of education, this requirement plays an extremely important role, since it allows one to find tools for the implementation of practical solutions in various segments of education and upbringing. However, the real state of pedagogical textual discourse demonstrates a lot of serious problems. Despite the types and regulations of empirical, theoretical and contextual substantiation long established in classical logic, the authors of scientific pedagogical texts often violate the framework of a meaningful and logically correct discourse. The arguments put forward are often unable to either confirm or refute the conclusions of the authors; sometimes they require serious additions and corrections. This seriously undermines the degree of trust of the reading community (both theorists and practitioners) in the conclusions proposed by the authors, reduces the public authority of pedagogical science and undermines faith in its ability to constructively influence educational practice. Therefore, the need for methodological "intervention" in the argumentative field of scientific pedagogy can be considered quite conditioned. Such a research initiative could be the first step on the trajectory of the return of pedagogy to meet the criterion of methodological correctness. This conclusion is supported by the studies of European philosophers of education, which, together with the authors' analysis, determines the relevance of the chosen topic of the article.Aim. The present research aims to identify and justify the typology of incorrect arguments in pedagogical texts; and to display the wide spread of incorrect arguments as a field for promising research activities.Results. The results of the study are a typology of incorrect arguments, including: a) arguments that are untenable and inadequate to the defended theses; b) arguments that require serious concretisation and detail; c) structurally complex arguments, which are partially adequate, but, otherwise, they require a radical revision. The typology is added by not being placed on a par with the above three types of arguments, denoted by the cliché "complex argumentation palette".Methodology and research methods. The research methods were: analysis of the Russian and foreign texts containing incorrect arguments; a selection of sources containing the most widespread argumentation errors; inductive generalisation to construct and substantiate the typology of incorrect arguments in pedagogy; reflection of the result obtained and identification of fragments of the designated topic that are relevant for prospective research.Scientific novelty. The scientific novelty lies in the transfer of the research focus from the traditional designation by pedagogy methodologists of the criteria for the correctness of pedagogical discourse arguments to the identification of a typology of methodologically incorrect arguments, including three adjacent elements, supplemented by an element in which the three above are intertwined in a complex way. The totality of the results obtained can be displayed as a "constructive prohibition" criterion, illustrating to the scientific community ways to justify the results that must be avoided.Practical significance. The practical significance of the results lies in the specific guidelines for incorrect arguments of scientific discourse, which can be metaphorically clichéd as an "example for non-imitation" and, on this basis, increase the degree of adequacy of the arguments to the thesis being defended in one's own texts.